Evidence for Graft versus Tumour Effect after Allogeneic Stem Cell Transplantation for Leukaemia and Lymphoma - Meutia Ayuputeri Kumaheri (PT. Kalbe Farma Tbk., 2017)
Haematopoietic Stem Cell Transplantation (HSCT) has been commonly used in the treatment of haematopoietic malignancy as a rescue regiment to prevent bone marrow toxicity subsequent to high dose chemotherapy.The harmful effects are leading to Graft versus Host Disease (GVHD). However, studies have shown that GVHD, T-Cell dependent mechanisms, and NK cells in allogeneic stem cell transplantation contributed to a lower risk of disease relapse by a mechanism known as Graft versus Tumour (GVT) effect. Evidence of Graft Versus Tumour (GVT) effect has allowed development of cancer therapy with less toxic chemotherapy to allow tumour eradication. This essay aims to discuss evidences of GVT effect after allogeneic stem cell transplantation in both leukaemia and lymphoma and examine future prospects of maximizing GVT effect in the treatment of both diseasesTransplantasi dengan sel punca hematopoietis umumnya digunakan untuk pengobatan keganasan darah sebagai pencegahan toksisitas kemoterapi dosis tinggi terhadap sumsum tulang. Efek negatif dikenal sebagai graft rejection dan Graft versus Host Disease (GVHD). Meskipun demikian, para ilmuwan menemukan efek Graft versus Tumour (GVT) yang dapat menurunkan risiko relaps melalui efek GVHD, mekanisme dependen sel T dan sel NK. Efek GVT ini memungkinkan pengembangan terapi kanker yang lebih aman. Tulisan ini membahas bukti efek GVT setelah tranplantasi sel punca alogenis pada leukemia dan limfoma serta propek masa depan untuk memaksimalkan efek GVT pada terapi leukemia dan limfoma.